Translation, sociolinguistic, and consumer issues in interpreting - Fleetwood, Earl; Metzger, Melanie, 1963- (Washington, D.C. : Gallaudet University Press, 2007)
This new volume focuses on scholarship over a refined spectrum of issues that confront interpreters internationally. Editors Melanie Metzger and Earl Fleetwood call upon researchers from the United States, Ireland, Australia, and the Philippines to share their findings in six chapters.
Handling and incorporation of idioms in interpretation / Roberto R. Santiago, Lisa Frey Barrick -- Deep and meaningful conversation : challenging interpreter impartiality in the semantics and pragmatics classroom / Lorraine Leeson, Susan Foley-Cave -- Initial observations on code-switching in the voice interpretations of two Filipino interpreters / Liza B. Martinez -- Indirectness strategies in American Sign Language requests and refusals : deconstructing the deaf-as-direct stereotype / Daniel Roush -- An invitation to dance : deaf consumers' perception of signed language interpreters and interpreting / Jemina Napier, Meg J. Rohan -- Use of space during and English-to-ASL interpretation when a visual aid is present / Amy Frasu.
Includes bibliographical references and index.
Keywords: Interpreters for the deaf; Translating and interpreting; Sign language -- Translating; Sociolinguistics; Sign language; Translating and interpreting